Mediating Role of Negative Emotion Regulation in the Relationship Between Avoidance and Prolonged Grief Disorder Syndrome - Armin Haq Nazari Esfahalan; Rahim Yousefi; Nadia Abbasi Gharibeh (مطالعات روانشناختی)
Grief is a stressful life event. Knowledge of the factors that influence the psychological outcomes of grief may help to improve treatment for bereaved individuals. This study aimed to investigate the mediating role of negative emotion regulation in the relationship between avoidance and prolonged grief disorder symptoms. The research design used a correlational approach with structural equation modeling. The study population consisted of students from Shahid Madani University during the 2023-2024 academic year. A sample of 311 students was selected via online recruitment in university channels and academic groups who participated in this study. The instruments were used included the Parker and Endler Coping Styles Questionnaire, the Cognitive Emotion Regulation Questionnaire, and the Prolonged Grief Questionnaire. Data analysis were conducted using the structural equation modeling method. The results revealed significant relationships between avoidance and negative emotion regulation, and between negative emotion regulation and prolonged grief. Additionally, avoidance, when mediated by negative emotion regulate on strategies such as rumination, blaming others, and catastrophizing, was found to predict prolonged grief disorder. The proposed model demonstrated a good fit. These findings could be useful for understanding and developing interventions for individuals experiencing prolonged grief.